2009
DOI: 10.1093/brain/awp076
|View full text |Cite
|
Sign up to set email alerts
|

Selective adenosine A2a receptor antagonism reduces JNK activation in oligodendrocytes after cerebral ischaemia

Abstract: Adenosine is a potent biological mediator, the concentration of which increases dramatically following brain ischaemia. During ischaemia, adenosine is in a concentration range (muM) that stimulates all four adenosine receptor subtypes (A(1), A(2A), A(2B) and A(3)). In recent years, evidence has indicated that the A(2A) receptor subtype is of critical importance in stroke. We have previously shown that 24 h after medial cerebral artery occlusion (MCAo), A(2A) receptors up-regulate on neurons and microglia of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 74 publications
2
54
0
Order By: Relevance
“…Thus, A 2A R are also located in astrocytes and microglia cells [238][239][240], where they can control glutamate clearance [94,241], the expression and action of trophic factors [242][243][244][245] and neuroinflammation [238,244,246,247]. Furthermore, A 2A R were also recently found to be present in oligodendrocytes, controlling their degeneration upon ischemia [248]. Probably both neuronal and non-neuronal mechanisms contribute to the ability of A 2A R to control neurodegeneration, according to their temporal pattern of recruitment: for instance, using the MPTP animal model of Parkinson's disease, it has been shown that damage caused by administration of higher doses of MPTP (causing a rapid neurodegeneration) is prevented by non-neuronal A 2A R blockade [240], whereas damage caused by administration of lower doses of MPTP (causing a slow and insidious neurodegeneration) is instead prevented by the genetic deletion of neuronal A 2A R [249].…”
Section: C Possible Role Of Adenosine a 2a Receptorsmentioning
confidence: 97%
“…Thus, A 2A R are also located in astrocytes and microglia cells [238][239][240], where they can control glutamate clearance [94,241], the expression and action of trophic factors [242][243][244][245] and neuroinflammation [238,244,246,247]. Furthermore, A 2A R were also recently found to be present in oligodendrocytes, controlling their degeneration upon ischemia [248]. Probably both neuronal and non-neuronal mechanisms contribute to the ability of A 2A R to control neurodegeneration, according to their temporal pattern of recruitment: for instance, using the MPTP animal model of Parkinson's disease, it has been shown that damage caused by administration of higher doses of MPTP (causing a rapid neurodegeneration) is prevented by non-neuronal A 2A R blockade [240], whereas damage caused by administration of lower doses of MPTP (causing a slow and insidious neurodegeneration) is instead prevented by the genetic deletion of neuronal A 2A R [249].…”
Section: C Possible Role Of Adenosine a 2a Receptorsmentioning
confidence: 97%
“…It has been claimed that A 2A receptor-stimulated cascade in bone marrow-derived cells is an important modulator of ischemic brain injury (Yu et al, 2004). A 2A receptor antagonism reduced JNK MAPK activation in oligodendrocytes after cerebral ischemia (Melani et al, 2010). In A 2A receptor knockout mice there was a decrease in early ischemic vascular injury after subarachnoid hemorrhage (Sehba et al, 2010).…”
Section: Ischemiamentioning
confidence: 99%
“…10 However, adenosine acting through A 2A receptors on oligodendrocytes could also have deleterious effects. 22 Paradoxically, both agonists and antagonists of α2 noradrenergic receptors improve WM recovery after ischemic/reperfusion injury, apparently by reducing axonal Na + and Ca 2+ accumulation. 14 Complex, but plausible, actions of these agents might explain these strange results.…”
Section: +mentioning
confidence: 99%
“…This review summarizes current knowledge of the molecular mechanisms of ischemic injury to WM and discusses its translational implications for the treatment of stroke (Table). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] …”
mentioning
confidence: 99%